Building Academic Reading Skills in Children with ASD Using the Author's Method "Speaking Skills" - N.A. Nikonova; Y.B. Pavlova; K.K. Danilina; K.R. Salimova; E.Y. Davydova (Moscow State University of Psychology and Education, 2022)
Speech deficits in autism spectrum disorders (ASD) can be observed at child’s early development in the form of a deficit in understanding addressed speech, abnormal prelinguistic development, and deficits in the communicative sphere. These factors further prevent children with ASD from successful building reading skills. With all the variety of reading difficulties in children with ASD, reading comprehension problems are the most common. At the same time, it has been repeatedly shown that the deficit in reading comprehension is based on the deficit of oral speech, and the volume of the vocabulary and the level of mastering the syntactic norms of the language play a big role. The colleagues of the Federal Resource Center for the Organization of Comprehensive Support to Children with ASD (FRC MSUPE) developed the author’s method called «Speaking Skills». It is aimed at developing reading skills in children with ASD. The method is intended for teaching preschoolers and younger schoolchildren in groups. The article describes the method implementation step by step, give the scheme of a typical lesson, as well as the criteria for assessing skills necessary for mastering the reading. We provide examples of original didactic materials that allow the child to “read” the sentence, knowing the minimum number of letters. It increases the child’s interest and motivation for classes. The technique of relying on one letter, which is a lexically significant unit, creates an attitude to reading as a process of extracting meaning, which increases learning effectiveness. It also describes how to adapt the program to the special educational needs of children with ASD: organization of educational environment; adaptation and the way of introducing the materials; coping with leading developmental challenges. The design of the planned pilot study of the effectiveness of the presented methodology is described. Thus, using the method “Speaking Skills” allow not only to more successfully master reading skills, but also to fill in the deficiencies in the communicative and social sphere.